A revision of the status of Lepadogaster lepadogaster (Teleostei: Gobiesocidae): sympatric subspecies or a long misunderstood blend of species? - Henriques, Miguel (2020)
Molecular (partial mitochondrial 12S ribosomal DNA sequences), morphological and meristic analysis of Lepadogaster lepadogaster lepadogaster, L. l. purpurea and L. zebrina were performed to investigate the relationships between these taxa. On the western shore of mainland Portugal, where the two subspecies of L. lepadogaster occur sympatrically, they differ in microhabitat preferences and their breeding seasons are largely out of phase. This information, combined with data on distribution patterns, led to the following conclusions: Lepadogaster l. purpurea is considered to be a valid species, L. purpurea (Bonnaterre, 1788), different from L. l. lepadogaster, now designated L. lepadogaster (Bonnaterre, 1788). L. zebrina was found to be a synonym of L. lepadogaster. The two newly defined species were found to be in sympatry at Madeira and the Canary islands, the Atlantic coast of the Iberian Peninsula, and the Mediterranean at least as far as Genoa (Italy). Diagnostic characters and a list of synonyms are provided. © 2002 The Linnean Society of London, Biological Journal of the Linnean Society, 2002, 76, 327–338.